Wali Nanggroe and Revitalization of Traditional Authority in The Modern Political System of Aceh - M Rizwan; Tunku Mohar Mokhtar; Muhammad bin Abubakar; Dahlan A Rahman; Bimby Hidayat (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
Studies on traditional institutions in Aceh have predominantly focused on their historical development, legal status, and political dynamics, while limited attention has been given to the transformation of traditional authority into a governance mechanism that sustains peace in post-conflict societies. This study examines how the revitalization of the Wali Nanggroe institution has extended beyond its conventional role as the guardian of Acehnese customs and cultural identity to become an institutional mechanism supporting sustainable peace within Aceh’s contemporary governance system. Employing a qualitative research design, the study integrates policy analysis and discourse analysis to examine legal frameworks, policy documents, the Helsinki Peace Agreement, and relevant scholarly literature. The data were analyzed interpretively to explore the institutional construction, legitimacy, and governance functions of Wali Nanggroe. The novelty of this study lies in its conceptualization of Wali Nanggroe as a form of hybrid governance, demonstrating how a traditional institution can mediate between customary authority, state institutions, and society to reinforce peacebuilding in a post-conflict context. The findings reveal that the institutionalization of Wali Nanggroe has strengthened the legitimacy of customary authority while providing an inclusive platform for mediation, social consolidation, and the preservation of social cohesion, all of which contribute to political stability in Aceh. Although the institution continues to face challenges related to accountability, transparency, and the delineation of institutional authority, it remains a strategic actor in maintaining sustainable peace. This study contributes to the literature on traditional authority, hybrid governance, and peacebuilding by demonstrating that the revitalization of customary institutions can serve as an effective governance mechanism for sustaining peace and strengthening governance in post-conflict societies.